Data thieves in action: examining the international market for stolen personal information - Holt, Thomas J. (Palgrave studies in cybercrime and cybersecurity series, 2016)
1. Introduction -- 2. The marketing and sales of stolen data -- 3. The economic impact of stolen data markets -- 4. The social organizations of actors in stolen data markets -- 5. Visualizing the networks of economic transactions and ads in stolen data markets -- 6. Implications and conclusions